Effects of Ozone and Ultraviolet on Physical and Oxidative Properties in Edible Coating’s Chicken Breast Meat. (Faculty of Animal Science Universitas Brawijaya, 2021)
The effects of gaseous ozone exposure on the physical and oxidative properties were evaluated in chicken breast fillets, which were pretreatment of gaseous ozone, ultraviolet, edible coatings and stored at 8°C (refrigerator), 27°C (closed pack), and 27°C (opened pack) for 4 d. The physical and oxidative properties of chicken meat are maintained after preozonation treatment is then applied to the edible coating. pH of chicken meat given ozone, UV and edible coating and stored at refrigerator that a pH closest to the normal chicken meat pH of 5.87. Combination of ozone, UV and edible coating has and the highest water holding capacity value and TBA value but the lowest cooking loss value. The brightness level of chicken meat coated in edible coating and stored at various temperatures showed a difference. The ability to store longer or with an increase in storage temperature, besides that, it can add value to the bioactive antioxidant and antimicrobial components.